Bacteremia caused by Veillonella dispar in an oncological patient. (December 2020) - Cobo, Fernando; Pérez-Carrasco, Virginia; García-Salcedo, José A.; Navarro-Marí, José María
Abstract: Veillonella dispar is a Gram-negative anaerobic coccus involved in only a few human diseases. We report the second case of bacteremia due to this microorganism in an elderly patient. A 72-year-old man with a history of bladder cancer presented with diarrhea, vomiting, and fever for 48 hours. After the diagnosis of septic shock, four sets of blood cultures were taken, and three of them yielded V. dispar. Resistance to metronidazole, penicillin, and piperacillin-tazobactam was documented. Treatment with clindamycin was started, and the patient was discharged after improvement in his general condition. Highlights: Veillonella dispar is rarely associated with bloodstream infections. This is the second case of bacteraemia caused by this pathogen in pure culture. Caution should be taken with anaerobes and mass spectrometry. The strain, as in other published cases, was resistant to metronidazole.